2021
DOI: 10.21203/rs.3.rs-798816/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asthma in Paediatric Intensive Care in England Residents: Observational Study

Abstract: Purpose Despite high prevalence of asthma in children in the UK, there are no prior report on asthma admissions in paediatric intensive care units (PICU). Methods PICANet, a UK national PICU database, was queried for asthma as the primary reason for admission, of children resident in England from April 2006 till March 2013. Results There were 2,195 admissions to PICU for a median stay of 1.4 days. 59% were males and 51% aged 0-4 years. The fourth and fifth deprivation quintiles represented 61% (1,329) admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Mukherjee et al studied the characteristics of children admitted at the PICU for asthma. They found that children from deprived neighborhoods comprised most of the PICU admissions (61%); moreover, these children also had the highest proportion of deaths and received mechanical ventilation most frequently 27 . However, they surprisingly reported an increase in the Pediatric Index of Mortality score (PIM2)-score for children that lived in lesser deprived areas, also after adjusting for age, sex and the year 27 .…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…Mukherjee et al studied the characteristics of children admitted at the PICU for asthma. They found that children from deprived neighborhoods comprised most of the PICU admissions (61%); moreover, these children also had the highest proportion of deaths and received mechanical ventilation most frequently 27 . However, they surprisingly reported an increase in the Pediatric Index of Mortality score (PIM2)-score for children that lived in lesser deprived areas, also after adjusting for age, sex and the year 27 .…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…They found that children from deprived neighborhoods comprised most of the PICU admissions (61%); moreover, these children also had the highest proportion of deaths and received mechanical ventilation most frequently 27 . However, they surprisingly reported an increase in the Pediatric Index of Mortality score (PIM2)-score for children that lived in lesser deprived areas, also after adjusting for age, sex and the year 27 . Another study on acute respiratory failure in England and Wales also reported a higher proportion of admitted infants coming from deprived areas 28 .…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms such as cough and wheeze in preschool‐aged children can be an early sign of asthma and cause a high burden of morbidity and health‐care utilization 1–4 . Asthma also remains an important cause of morbidity later in childhood 5,6 . To reduce childhood asthma morbidity and overtreatment, it is important for clinicians to identify children with asthma early.…”
Section: Introductionmentioning
confidence: 99%